Clinical and functional recovery of patients with chronic knee pain according to the WOMAC index - Kirpichnikova, Kateryna (Journal of Education, Health and Sport, 2026)
Introduction. Knee osteoarthritis is one of the most common chronic degenerative musculoskeletal disorders and a leading cause of chronic pain, functional impairment, and reduced quality of life. One of the most promising minimally invasive treatment options is genicular nerve radiofrequency ablation (RFA), which provides prolonged analgesic effects and improves functional outcomes. However, further investigation is needed to evaluate the clinical and functional recovery of patients of different sexes and age groups following RFA combined with a multidisciplinary treatment and rehabilitation approach. Objective. To evaluate the clinical and functional recovery of patients with chronic knee pain following genicular nerve radiofrequency ablation within a multidisciplinary treatment approach based on the analysis of changes in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Materials and methods. A retrospective-prospective clinical study was conducted involving 49 patients with clinically and instrumentally confirmed knee osteoarthritis (28 women, 57.1%, and 21 men, 42.9%) aged 45–75 years. All patients underwent ultrasound-guided genicular nerve radiofrequency ablation followed by multidisciplinary treatment, including pharmacological therapy, physical therapy, therapeutic exercise, controlled physical activity, and continuous clinical follow-up. Treatment effectiveness was assessed using the WOMAC index before the intervention and at 1, 3, and 6 months after the procedure. Statistical analysis was performed using descriptive statistics, one-way analysis of variance (ANOVA), the paired Student's t-test, and Fisher's test, with statistical significance set at p < 0.05. Results and conclusions. A statistically significant improvement in the clinical and functional status of patients was observed throughout the six-month follow-up period. In women, WOMAC scores decreased from 61.3–72.2 points at baseline to 30.7–43.8 points after 6 months, whereas in men they decreased from 65.7–79.7 to 33.7–52.9 points. The greatest improvement was observed during the first month after RFA, with WOMAC scores decreasing by an average of 20–30% compared with baseline, followed by sustained improvement at 3 and 6 months. No association was found between treatment effectiveness and patient age, while the statistical significance of the findings was confirmed using ANOVA, Student's t-test, and Fisher's test (p < 0.05). Genicular nerve radiofrequency ablation combined with a multidisciplinary approach is an effective and safe treatment for chronic pain associated with knee osteoarthritis. The procedure provides a statistically significant and sustained reduction in pain severity, improves functional status and quality of life regardless of patients' age or sex, and can therefore be recommended as an effective component of comprehensive treatment and rehabilitation for patients with knee osteoarthritis.